A study of developments and applications of mixed reality cubicles and their impact on learning. Issue 1 (16th September 2019) - Uhomoibhi, James; Onime, Clement; Wang, Hui
Abstract : Purpose: The purpose of this paper is to report on developments and applications of mixed reality cubicles and their impacts on learning in higher education. This paper investigates and presents the cost effective application of augmented reality (AR) as a mixed reality technology via or to mobile devices such as head-mounted devices, smart phones and tablets. Discuss the development of mixed reality applications for mobile (smartphones and tablets) devices leading up to the implementation of a mixed reality cubicle for immersive three dimensional (3D) visualizations. Design/methodology/approach: The approach adopted was to limit the considerations to the application of AR via mobile platforms including head-mounted devices with focus on smartphones and tablets, which contain basic feedback–to-user channels such as speakers and display screens. An AR visualization cubicle was jointly developed and applied by three collaborating institutions. The markers, acting as placeholders acts as identifiable reference points for objects being inserted in the mixed reality world. Hundreds of participants comprising academics and students from seven different countries took part in the studies and gave feedback on impact on their learning experience. Findings: Results from current study show less than 30 percent had used mixed reality environments. This is lower than expected. About 70 percent of participants were first time users of mixed reality technologies. This indicates a relatively low use of mixed reality technologies in education. This is consistent with research findings reported that educational use and research on AR is still not common despite their categorization as emerging technologies with great promise for educational use. Research limitations/implications: Current research has focused mainly on cubicles which provides immersive experience if used with head-mounted devices (goggles and smartphones), that are limited by their display/screen sizes. There are some issues with limited battery lifetime for energy to function, hence the need to use rechargeable batteries. Also, the standard dimension of cubicles does not allow for group visualizations. The current cubicle has limitations associated with complex gestures and movements involving two hands, as one hand are currently needed for holding the mobile phone. Practical implications: The use of mixed reality cubicles would allow and enhance information visualization for big data in real time and without restrictions. There is potential to have this extended for use in exploring and studying otherwise inaccessible locations such as sea beds and underground caves. Social implications – Following on from this study further work could be done to developing and application of mixed reality cubicles that would impact businesses, health and entertainment. Originality/value: The originality of this paper lies in the unique approach used in the study of developments and applications of mixed reality cubicles and their impacts on learning. The diverse composition in nature and location of participants drawn from many countries comprising of both tutors and students adds value to the present study. The value of this research include amongst others, the useful results obtained and scope for developments in the future.